Continuous management training - Benussi, Fulvio Oscar (Community Notebook. People, Education and Welfare in the Society 5.0, 2022)
With the Marshall Plan, in the years following the Second World War, management schools in the post-university segment also spread in Italy and were characterised by the overcoming of the deductive method and lectures, gradually replaced or supplemented with active teaching methods. This is how management schools such as SDA Bocconi, the Milan Polytechnic, etc. came into being. It was in this sphere that the commitment of associations, including ASFOR, to promoting quality management training subsequently took place.